Quality of Wood and Charcoal from Eucalyptus Clones for Ironmaster Use - Bárbara Luísa Corradi Pereira; Aylson Costa Oliveira; Ana Márcia Macedo Ladeira Carvalho; Angélica de Cássia Oliveira Carneiro; Larissa Carvalho Santos; Benedito Rocha Vital (International Journal of Forestry Research)
Considering the wide variety of species and clones of Eucalyptus cultivated in Brazil, it is necessary to search for new information on wood properties, so that the selection of genetically superior material may be successful. The present study aimed to determine the properties of wood and charcoal from different clones of Eucalyptus spp. Six clones at the age of 7.5 years were evaluated and the samples were from a clonal, located in the city of Lassance, Minas Gerais, Brazil. Basic density, chemical composition, and higher heating value were determined. Carbonizations in a laboratory kiln were done and the levels of volatile matter, ash, and fixed carbon, higher heating value, and bulk density of the charcoal produced were determined. Evaluated genetic materials showed differences in their properties. According to research results, several properties of wood should be considered together for the selection of clones for charcoal production. However, basic density and chemical composition of wood, especially high contents of lignin and low contents of extractives, are the properties that had more influence on charcoal yield and its quality. Concerning charcoal production for steelmaking, clone 6 stood out and, conversely, clone 4 showed inferior properties to those of others.